Cover Image. (13th September 2018) - Liu, Yang; Zhang, Xianli; Sun, Xiangyu; Wang, Xiaozhe; Zhang, Chenying; Zheng, Shuguo
Abstract : The cover image, by Yang Liu et al., is based on the Original Article Abnormal bone remodelling activity of dental follicle cells from a cleidocranial dysplasia patient, DOI:10.1111/odi.12900 .